Teaching English as an International Language (EIL) in Nepal - Mohan Singh Saud (Institut Agama Islam Negeri Palopo, 2020)
With the rapid growth and widespread use of English worldwide, there has been a paradigm shift from teaching English as foreign language to teaching English as an international language. However, there has been less discussion on English pedagogy about the global spread of English in this era of globalization, with rapid increase of English speakers around the world. The internationalisation of the status of English, leading to the emergence of World Englishes, has led to discuss the issue of teaching English as an international language (TEIL) to visit the way we conceptualise and teach English. As English is no longer a homogeneous language, English teachers across the world have been teaching English according to their own contexts. Considering this scenario, this article discusses teaching and learning of English as an international language in the context of Nepal, taking Kachru’s three concentric circles of English in the global context as the theoretical framework and English as an international language as the conceptual framework, focusing on use of culturally sensitive EIL pedagogy.